Clinical manifestations of cardiovascular disease in children as a sequela of coronavirus disease (COVID-19) (a clinical case) - Yu. V. Horodkova; M. Yu. Kurochkin; A. H. Davydova; O. I. Podlianova (Zaporožskij Medicinskij Žurnal)
The aim of the work: to provide medical practitioners with a clinical case of cardiovascular affection with ST-segment elevation in a child as a result of coronavirus disease (COVID-19).